ANALYSIS OF IMPLEMENTATION OF PSAK 71 AGAINST RESERVE LOSS OF IMPAIRMENT WHEN COVID-19 PANDEMIC IN PT. BANK CENTRAL ASIA TBK - Dithasya Anava Syabani Anissa; Tommy Kuncara; Bernardus Wishman S. Siregar (International Journal Management and Economic, 2022)
This study aims to analyze the implementation of PSAK 71 against impairment loss reserves during the Covid-19 pandemic in banking. The object of research on scientific writing is PT. Bank Central Asia Tbk. The types of data used in this research are qualitative and quantitative data. Sources of data used in this study is secondary data obtained from the company's official website. The data collection techniques used are literature studies and documentation techniques in the form of financial statements of PT. Bank Central Asia Tbk 2020. The results of this study showed that the bank has implemented PSAK 71 since January 1, 2020 in forming CKPN using the expected loss method which is reclassified using the business model method and SPPI testing first. Each reporting date period PT. Bank Central Asia Tbk will measure the loss reserve for financial instruments based on the amount of finance based on the amount of ECL-Lifetime (the number of expected credit losses throughout life) due to an indication of increased credit risk, the bank will put credit risk into stage 2 and Bank BCA calculates CKPN using ECL lifetime so that the formation of Bank BCA CKPN becomes larger. Judging from the number of CKPN in the 2020 financial statements decreased signaling better credit growth.